TREM-1 Modulation Strategies for Sepsis - Siskind, Sara; Brenner, Max; Wang, Ping (Frontiers in Immunology, 2022)
The triggering receptor expressed on myeloid cells-1 (TREM-1) is a pattern recognition receptor, which can be upregulated in inflammatory diseases as an amplifier of immune responses. Once activated, TREM-1 induces the production and release of pro-inflammatory cytokines and chemokines, in addition to increasing its own expression and circulating levels of the cleaved soluble extracellular portion of TREM-1 (sTREM-1). This amplification of the inflammatory response by TREM-1 has now been considered as a critical contributor to the dysregulated immune responses in sepsis. Studies have shown that in septic patients there is an elevated expression of TREM-1 on immune cells and increased circulating levels of sTREM-1, associated with increased mortality. As a result, a considerable effort has been made towards identifying endogenous ligands of TREM-1 and developing TREM-1 inhibitory peptides to attenuate the exacerbated inflammatory response in sepsis. TREM-1 modulation has proven a promising strategy for the development of therapeutic agents to treat sepsis. Therefore, this review encompasses the ligands investigated as activators of TREM-1 thus far and highlights the development and efficacy of novel inhibitors for the treatment of sepsis and septic shock.